Synopsis of Paxillus MacLeay, 1819 (Coleoptera: Passalidae): distributional records and descriptions of four new species from Brazil - Mattos, Ingrid; Mermudes, José Ricardo M. (Zootaxa, 2013)
Paxillus MacLeay, 1819 (Coleoptera: Passalidae) is redescribed, with new distributional records and descriptions of four species from Brazil. Paxillus reyesi new species is characterized by the first antennomere of antennal club reduced, slight-ly longer than half of the second antennomere; mesosternal scar straight, wide and deep. Paxillus chapadensis new species from the Chapada dos Guimarães (Mato Grosso, Brazil) has prostenal process centrally impressed with an opaque depres-sion; and the scape of the antenna with a subapical dorsal spine, shallow ventral depression, and few erect setae. Paxillus manausensis new species from Manaus (Amazonas, Brazil) has high frontal ridges; mid-frontal tubercles high, acuminate and larger than the internal tubercles; and the central tubercle short. Paxillus uaupesensis new species from Uaupes (Am-azonas, Brazil) has the mesosternal scar opaque, elongate and depressed; and the scutellum depressed. Diagnostic rede-scriptions and illustrations of known species from Brazil, a key to all known species, and a checklist with distributional data are provided.